The impact of childhood health on adult labor market outcomes - James P. Smith (Institute for the Study of Labor (IZA), 2009)
This paper examines impacts of childhood health on SES outcomes observed during adulthood-levels and trajectories of education, family income, household wealth, individual earnings and labor supply. The analysis is conducted using data that collects these SES measures in a panel who were originally children and who are now well into their adult years. Since all siblings are in the panel, one can control for unmeasured family and neighborhood background effects. With the exception of education, poor childhood health has a quantitatively large effect on all these outcomes. Moreover, these estimated effects are larger when unobserved family effects are controlled.
urn:nbn:de:101:1-2009082030
Keywords: I10; J00; 330; Childhood health; labor market outcomes; Gesundheit; Kinder; Lohn; Sozialer Status; Irland